High-dose methotrexate-based immuno-chemotherapy for elderly primary CNS lymphoma patients (PRIMAIN study) - Fritsch, Kristina; Löw, Sarah (Leukemia, 2017)
To investigate immuno-chemotherapy for elderly immuno-competent patients (65 years) with newly diagnosed primary central nervous system lymphoma, we conducted a multicentre single-arm trial. One cycle consisted of rituximab (375 mg/m2, days 1, 15, 29), high-dose methotrexate (3 g/m2 days 2, 16, 30), procarbazine (60 mg/m2 days 2-11) and lomustine (110 mg/m2, day 2)—R-MPL protocol. Owing to infectious complications, we omitted lomustine during the study and consecutive patients were treated with the R-MP protocol. Three cycles were scheduled and repeated on day 43. Subsequently, patients commenced 4 weekly maintenance treatment with procarbazine (100 mg for 5 days). Primary end point was complete remission (CR) after 3 cycles. We included 107 patients (69 treated with R-MPL and 38 with R-MP). In all, 38/107 patients achieved CR (35.5%) and 15 (14.0%) achieved partial remission. R-MP was associated with a lower CR rate (31.6%) compared with R-MPL (37.7%), but respective 2-year progression-free survival (All 37.3%; R-MP 34.9%; R-MPL 38.8%) and overall survival (All 47.0%; R-MP 47.7%; R-MPL 46.0%) rates were similar. R-MP was associated with less grade 3 toxicities compared with R-MPL (71.1% vs 87.0%). R-MP is more feasible while still associated with similar efficacy compared with R-MPL and warrants further improvement in future studies.